Pengaruh Penggunaan Animasi Dalam Game Edukasi Terhadap Minat Belajar Murid Sekolah Dasar - Hamonangan, Ryan; Danar Dana, Raditya; Arumsari, Rahayu (CV. Multi Kreasi Media, 2024)
The use of educational games today continues to be a teaching material that is in demand by teachers, with this learning method it can foster the creativity of students to improve the quality of education better. Educational games have the aim of stimulating the intelligence of the child's brain, as a counterweight to the right brain and the left brain. In addition, by using educational games, it has an interesting and useful concept, so that students feel happy and can find new things in it. The problem in this study for Indonesian lessons is that students prefer the material visually or with animated images, because as teachers, they must also be able to adjust the mood of students. Basically, this educational game is like playing but there are still lessons to be learned. The purpose of this study is to make an interesting educational game so that students in this elementary school can be more enthusiastic about learning. The method used is ADDIE (Analysis, Design, Development, Implementation, Evaluation), this model can be used for a variety of learning activity products and with this educational game can be the material for evaluating the final value. The results of this study are based on the results in making animated games using Smart Apps Creator software, resulting in games that are easy to use for grade 2 elementary school students. From the test calculated using the CALCULATION OF SUS (system usability scale) from 24 respondents the assessment given for the feasibility of educational games Indonesian obtained a score of 82, With Acceptability Ranges obtained Acceptable, the Adjectives Rating version includes the Best imaginable grade and Interpretation with a Grade Scale, then a score of 82 is included in the rating (A).